International Law and Search and Rescue - Button, Rick (U.S. Naval War College Digital Commons, 2018)
The search for and rescue of persons in distress is a centuries-old, time- honored tradition. The above instructions provided to Captain Francis Tut- tle of the U.S. Revenue Cutter Service over a century ago, as he prepared his crew to rescue whalers trapped in ice in the Arctic Ocean, epitomize the dedicated efforts of mariners and coastal states in saving lives at sea.